Incidence and impact of acute kidney injury on patients with implantable left ventricular assist devices: a Meta-analysis. Issue 1 (1st January 2020) - Thongprayoon, Charat; Lertjitbanjong, Ploypin; Cheungpasitporn, Wisit; Hansrivijit, Panupong; Fülöp, Tibor; Kovvuru, Karthik; Kanduri, Swetha R.; Davis, Paul W.; Vallabhajosyula, Saraschandra; Bathini, Tarun; Watthanasuntorn, Kanramon; Prasitlumkum, Narut; et al.
Abstract: Background: We aimed to evaluate the acute kidney injury (AKI) incidence and its associated risk of mortality in patients with implantable left ventricular assist devices (LVAD). Methods: A systematic literature search in Ovid MEDLINE, EMBASE, and Cochrane Databases was conducted through January 2020 to identify studies that provided data on the AKI incidence and AKI-associated mortality risk in adult patients with implantable LVADs. Pooled effect estimates were examined using random-effects, generic inverse variance method of DerSimonian-Laird. Results: Fifty-six cohort studies with 63, 663 LVAD patients were enrolled in this meta-analysis. The pooled incidence of reported AKI was 24.9% (95%CI: 20.1%–30.4%) but rose to 36.9% (95%CI: 31.1%–43.1%) when applying the standard definition of AKI per RIFLE, AKIN, and KDIGO criteria. The pooled incidence of severe AKI requiring renal replacement therapy (RRT) was 12.6% (95%CI: 10.5%–15.0%). AKI incidence did not differ significantly between types of LVAD ( p  = .35) or indication for LVAD use ( p  = .62). While meta-regression analysis did not demonstrate a significant association between study year and overall AKI incidence ( p  = .55), the study year was negatively correlated with the incidence of severe AKI requiring RRT (slope = −0.068, p  < .001). The pooled odds ratios (ORs) of mortality at 30 days and one year in AKI patients were 3.66 (95% CI, 2.00–6.70) and 2.22 (95% CI, 1.62–3.04), respectively. The pooled ORs of mortality at 30 days and one year in severe AKI patients requiring RRT were 7.52 (95% CI, 4.58–12.33) and 5.41 (95% CI, 3.63–8.06), respectively. Conclusion: We found that more than one-third of LVAD patients develop AKI based on standard definitions, and 13% develop severe AKI requiring RRT. There has been a potential improvement in the incidence of severe AKI requiring RRT for LVAD patients. AKI in LVAD patients was associated with increased 30-day and 1 year mortality.